Families of Children with Intellectual and Developmental Disabilities: Variables Associated with Family Quality of Life - Ghaleb H. Alnahdi; Susanne Schwab (MDPI AG, 2024)
Families of children with intellectual and developmental disabilities often face unique challenges that significantly impact their quality of life. Understanding the predictors of family quality of life (FQOL) is crucial for developing effective support systems and interventions. Aim: This study investigated the predictors that might influence the perception of families having a member with a disability regarding their quality of life (FQOL). Method: The sample consisted of 320 family members from the Riyadh region of Saudi Arabia. Results: The overall results showed that participants' satisfaction with FQOL was at a moderate level. Further results indicated that variables associated with severity, type of disability, and the mother's age and education were significant predictors of the FQOL. Conclusions: These results emphasize the importance of considering the variables that impact FQOL, such as the severity and type of disability, and mother's related variables, when directing support to families with a member with a disability. The recommendations and limitations of the study were discussed.